Ocular Surface Changes After Switching from Other Prostaglandins to Tafluprost and Preservative-Free Tafluprost in Glaucoma Patients - Ruangvaravate, Ngamkae (Clin Ophthalmol, 2020)
PURPOSE: To study ocular surface disease (OSD) changes after switching from preserved prostaglandin analogues monotherapy to preserved tafluprost and preservative-free (PF) tafluprost in primary open-angle glaucoma patients. METHODS: Glaucoma patients treated with preserved prostaglandins (except tafluprost) monotherapy for at least 6 months, intraocular pressure (IOP) ≤22 mmHg, and diagnosed of OSD [≥1 criterion; tear break-up time (TBUT) ≤10 seconds, corneal fluorescein staining ≥grade 1] in both eyes were enrolled in a prospective, randomized, single-blinded study. All eligible patients were switched from preserved prostaglandin analogues monotherapy (latanoprost, bimatoprost, travoprost) to preserved tafluprost in one eye (group I) and PF-tafluprost in the other eye (group II) of the same patient by randomization. The symptoms of OSD were evaluated using the visual analogue scale, and lid inflammation, conjunctival hyperemia, TBUT, corneal fluorescein staining, and Schirmer I test were applied to assess the clinical signs. All parameters were evaluated before and then 6, 12, 24 weeks after switching the medications. RESULTS: Thirty patients (80% women; mean age: 61.2 ±11.5 years) were included. Baseline parameters were not different between the treatment groups. After switching therapies, TBUT was significantly increased in both groups (p = 0.002, p = 0.004, respectively); however, group II had better tear quality. Other symptoms and clinical signs of OSD were improved and IOP was controlled in both groups. CONCLUSION: Treatment with PF-tafluprost improves TBUT better than preserved tafluprost, suggesting that PF-tafluprost should be especially beneficial for patients with pre-existing OSD. Less or no preservative anti-glaucoma eye drops can restore and enhance the ocular surface in glaucoma patients.